2018
DOI: 10.3389/fpsyt.2018.00354
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Abuse and Indicators of Immune Activity: A Systematic Review

Abstract: Background: Childhood sexual abuse (CSA) is a prevalent subtype of early life stress associated with changes in immunological and neuroendocrine systems leading to inflammatory responses of the organism and increasing several inflammatory and immune markers. We aimed to conduct a systematic review concerning the association between CSA and indicators of immune activity.Methods: We conducted a search for articles in PubMed, Scopus, PsycINFO, and Web of Science, using the key words: (“Child sexual abuse” OR “chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 79 publications
(169 reference statements)
0
15
0
Order By: Relevance
“…CSA was shown to induce negative outcomes by contributing to structural brain changes such as the reduction of cortical thickness in ventromedial and ventrolateral prefrontal cortex and medial and lateral temporal cortex (Gold et al, 2016); these changes were related to mental diseases in later life (Cross et al, 2017). Furthermore, CSA was shown to be associated with upregulation of immune activity (D’Elia et al, 2018), which may even accelerate telomere erosion (Li et al, 2017).…”
mentioning
confidence: 99%
“…CSA was shown to induce negative outcomes by contributing to structural brain changes such as the reduction of cortical thickness in ventromedial and ventrolateral prefrontal cortex and medial and lateral temporal cortex (Gold et al, 2016); these changes were related to mental diseases in later life (Cross et al, 2017). Furthermore, CSA was shown to be associated with upregulation of immune activity (D’Elia et al, 2018), which may even accelerate telomere erosion (Li et al, 2017).…”
mentioning
confidence: 99%
“…The complexity of this evaluation is well demonstrated in a recent systematic review that aimed to describe the association between CSA and indicators of immune activity. The diversity in studies that were collected, and the heterogeneity of CSA and trauma assessments prevented a meta-analysis from being performed ( D’Elia et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The association between childhood sexual abuse and the development of persistent oxidative stress and inflammation is difficult to assess despite the existence of a plethora of studies investigating the subject. Some authors have reported an increase in both parameters in the short term but not in the long term while other authors have reported no difference compared with age- and sex-matched children with no history of such experiences [258, 259] (reviewed in [260]). The relationship between childhood maltreatment and the development of persistent oxidative stress appears to be much clearer however despite the difficulties in consistently defining the term [259, 261–263].…”
Section: Other Putative Pathological Consequences Of Elevated Pics Rmentioning
confidence: 99%